Emotional Labor in Teaching Chinese as an Additional Language in a Family-Based Context in New Zealand: A Chinese Teacher’s Case - Bao, Chunrong; Zhang, Lawrence Jun; Dixon, Helen R. (Frontiers in Psychology, 2022)
New Zealand is a multilingual and multicultural society, where English, Maori and the New Zealand sign language are designated as its official languages. However, some heritage languages (e.g., Chinese/Mandarin Chinese, French, German, Japanese, Korean, among others) are also taught either within or outside the national education system. During the past decade, an increasing number of students have chosen Mandarin Chinese (hereafter “Chinese”) as an additional language (CAL) because of its fast-growing importance. To date, studies regarding CAL are mainly based on the mainstream Chinese programs (i.e., in schools or universities) or online platforms, with little attention paid to other types of teaching contexts (e.g., family-based context, private tutoring contexts, etc.) where there also exist many potential challenges awaiting teachers. To fill in this gap, this study, based on a teaching program consisting of two families in New Zealand, explored the trajectories of a CAL teacher’s emotional labor for 47 weeks to understand how she managed her emotions when she taught the language as well as balanced the relationship among the three parties: the institution, the two families, and herself. Narrative inquiry was used as a methodological approach. The data involved written and spoken narratives. Using inductive and deductive thematic analysis, findings revealed her different understandings of the emotional labor in the two families respectively during the course of the program. Further analysis of the data revealed some factors that impacted her emotional labor and how they impacted her teaching in a family-based context. We concluded our study with a discussion of the implications of these findings for teaching CAL in similar contexts.